Mysterious role of H3K56ac in embryonic stem cells - Stejskal, S; Tesařová, L; Koutná, I (Folia biologica, 2014)
Posttranslational modifications of histones belong to epigenetic mechanisms that regulate gene expression by chromatin structure changes. Generally, histone acetylation reduces its positive charge and consequently weakens the stability of the nucleosome. Acetylation of lysine 56 on histone H3 is implicated in the processes associated with loosened chromatin structure. H3K56ac is a mark for histones with high nucleosome turnover in the nuclear processes such as gene transcription, DNA replication and reparation in yeasts. During evolution, the main H3K56ac regulatory pathway was lost and the level of H3K56ac remained very low in mammalian cells. Moreover, the function of this modification still remains unclear. In this minireview, we summarize the recent knowledge of the ambiguous role of H3K56ac in mammalian embryonic stem cells.
Keywords: embryonální kmenové buňky; savci; Acetylation; lysin; acetylace; Lysine; Animals; Humans; Embryonic Stem Cells; lidé; zvířata; histony; Histones; Mammals